1993
DOI: 10.1002/art.1780360120
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of adjuvant‐induced arthritis in da rats by incomplete freund's adjuvant

Abstract: Objective. To define the effects of incomplete Freund's adjuvant (LCFA) on subsequent arthritis induced by complete Freund's adjuvant (CFA) and type I1 collagen (CII) in DA and Lewis rats.Methods. ICFA was injected into DA and Lewis rats before CFA or CII injection.Results. DA rats previously injected with ICFA had significantly less severe arthritis induced by CFA compared with those not receiving ICFA pretreatment (P < 0.01). ICFA had no significant impact on CFAinduced arthritis in Lewis rats or on CII-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 11 publications
0
35
1
Order By: Relevance
“…No sex differences in degree of joint inflammation and disease course were observed. In rats of the DA strain, several substances with known arthritogenic effects, including IFA, can induce severe arthritis (15,24,25). Injection of IFA with CpG added did not increase the disease severity compared with IFA alone, and CpG administered in PBS did not induce disease in the DA rat.…”
Section: Discussionmentioning
confidence: 92%
“…No sex differences in degree of joint inflammation and disease course were observed. In rats of the DA strain, several substances with known arthritogenic effects, including IFA, can induce severe arthritis (15,24,25). Injection of IFA with CpG added did not increase the disease severity compared with IFA alone, and CpG administered in PBS did not induce disease in the DA rat.…”
Section: Discussionmentioning
confidence: 92%
“…Many other rat strains have been tested for disease susceptibility and were found to vary dramatically. Most strains are resistant to OIA and only the DA and the DXEA strains develop a mild acute arthritis (33,34,40). The DXEA strain contains DA genes since it is a recombinant inbred of E3 and DA.…”
Section: Genetic Control Of Adjuvant Arthritis Modelsmentioning
confidence: 99%
“…The role of the MHC region in many of these models (OIA, AvIA, PIA and SIA) has been addressed using already established congenic strains on the LEW or DA background as well as in F2 crosses (6,33,40,78,92). Thus, studies of PIA have confirmed an MHC association (denoted Pia1) in both congenic strains and F2 crosses (6,92).…”
Section: Role Of the Major Histocompatibility Complexmentioning
confidence: 99%
See 2 more Smart Citations